2020
DOI: 10.3390/antibiotics9110788
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Fatty Acids Control Biofilm Formation of Staphylococcus aureus and Other Gram-Positive Bacteria

Abstract: Infections involving biofilms are difficult to treat due to increased resistances against antibiotics and the immune system. Hence, there is an urgent demand for novel drugs against biofilm infections. During our search for novel biofilm inhibitors from fungi, we isolated linoleic acid from the ascomycete Hypoxylon fragiforme which showed biofilm inhibition of several bacteria at sub-MIC concentrations. Many fatty acids possess antimicrobial activities, but their minimum inhibitory concentrations (MIC) are hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…Another explanation of PUFA toxicity may be related to metabolic imbalances in acyl CoA metabolism [ 62 ]. Remarkably, recent evidence subverts the aforementioned assumptions, indicating that unsaturated fatty acids did not considerably affect bacterial growth of both Gram-negative and -positive strains [ 63 ], whilst unsaturated fatty acids are involved in the prevention of biofilm formation in Gram-positive bacteria, even at the lowest treated level [ 63 ]. Hence, rumen bacteria populations could return to a planktonic lifestyle if the biofilm is dispersed, making them prone to abiotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation of PUFA toxicity may be related to metabolic imbalances in acyl CoA metabolism [ 62 ]. Remarkably, recent evidence subverts the aforementioned assumptions, indicating that unsaturated fatty acids did not considerably affect bacterial growth of both Gram-negative and -positive strains [ 63 ], whilst unsaturated fatty acids are involved in the prevention of biofilm formation in Gram-positive bacteria, even at the lowest treated level [ 63 ]. Hence, rumen bacteria populations could return to a planktonic lifestyle if the biofilm is dispersed, making them prone to abiotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…This ability may alter the degradation rate of starch in the rumen and consequently its digestibility and propionate production [ 53 ]. Considering that recent studies demonstrate that unsaturated fatty acids such as these presented in microalgae biomass could prevent the formation of bacterial biofilm returning them into a planktonic lifestyle [ 12 ], while ciliate protozoa appear to be the major planktonic bacterial predators [ 54 ], it is plausible to assume that the bacteria abundance may be suppressed in the 20HG-fed goats due to protozoa grazing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the inhibition of cellulolytic bacteria in presence of PUFA, there is strong evidence involving severe toxicity of PUFA on the cell membrane particularly of Gram-positive bacteria resulting in metabolic imbalances [ 10 , 11 ]. Additionally, recent evidence proposes that PUFA toxicity does not lie in bacteria disruption per se rather in the prevention of the biofilm formation in Gram-positive bacteria [ 12 ]. In contrast, the mechanism underlies the F:C on ruminal bacteriome appears to be more well-studied as lie in changes in pH [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study made by Harvey et al (2019) has revealed the biofilm inhibitory efficacy of antibacterial lipids on the cariogenic organism Streptococcus mutans by Fluorescent Microscopy using Alexa Fluor ® 647 and SYTO ® 9-labeled dextran conjugate. Further, the biofilm development of Gram-positive bacterial pathogens such as S. epidermidis, S. aureus , and S. mutans has been effectively inhibited by some unsaturated fatty acids such as oleic acid, linoleic acid, and palmitoleic acid ( Yuyama et al, 2020 ). The inhibitory efficacy of the two fatty acids includes docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) against Fusobacterium nucleatum and Porphyromonas gingivalis biofilms were recently studied by Sun et al (2016) .…”
Section: Recent Therapeutic Strategies For Biofilm Inhibitionmentioning
confidence: 99%